Electroless Plating of PLA and PETG for 3D Printed Flexible Substrates. (17th July 2015) - Bernasconi, Roberto; Natale, Gabriele; Levi, Marinella; Magagnin, Luca
Abstract : The NiP and Cu electroless metallization of 3D printed polymers is presented. The plating process is tested on suitable samples, which reproduce the printing morphologies used in the 3d printing of objects. An alkaline etching is used for both the polymers in order to modify the surface properties and enhance the adhesion and uniformity of the metallic coating. For the activation of the surface a tin free process involving an immersion in palladium and subsequent reduction to form metallic nuclei is employed. The Cu and NiP bath are selected to operate in temperature ranges comparable to the glass transition temperatures of the polymers. Adherent and uniform layers of NiP (3-4 % P wt.) and Cu can be easily obtained for esthetic and functional applications.